The discontinuation of antitumor treatment and the advance directives in cancer patients - Buiar, Pedro Grachinski; Goldim, Jose Roberto; Hirakata, Vania Naomi (Brazilian Journal of Oncology, 2020)
Objectives: Advance directives (AD) are one of the main pillars of patients' autonomy and can impact directly the quality of life, dignity and rights of the dying patient. Despitethis, advance directives face many barriers to be created, implemented and followed. The moment of discontinuation of active anticancer therapy is an important landmark in the palliative evolution of cancer patients. The aim of this study is to investigate if the discontinuation of antitumor treatment could influence rates of advance directives. Methods: A single-center retrospective case-notes review study with 321 randomly selected patients of a Single Brazilian tertiary oncology center. Qualitative and quantitative data were collected and analyzed to compare two groups of patients, one group with advance directives registered and another group without directives. Results: The rate of advance directives was 22.7%, and in 82.3% of subjects, the decision of treatment discontinuation occurs on the same day or before the AD manifestation. In multivariable analysis, 82.5% of patients with advance directives were in the doctor's office at the occasion of the discontinuation of their anticancer therapy compared with 64.4% of the patients without directives (RR 1.88; 95%CI 1.019-3.496). The most cited “living will” was the desire “to die at home” (30%), and 10% of those manifesting this directive actually died at home. Conclusion: The discontinuation of antitumor treatment may be a window for end of life and advance care plan discussions, raising the rates of advance directives. Doctor's office is a better place than emergency rooms, wards and intensive care units for the discussion about end of life aspects and advance directives.
Keywords: Advance directives; Medical oncology; Palliative care; Living wills